Method for repairing solid electrolyte, solid electrolyte sheet and battery

Through microwave heat treatment technology and the use of bismuth oxide or molybdenum oxide modifiers, solid electrolytes are repaired in situ, solving the problems of its air instability and large interface impedance, and significantly improving its ionic conductivity and battery performance.

CN119725702APending Publication Date: 2025-03-28深圳毅华新能源有限公司 +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411966461.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Solid electrolytes are unstable in the air and are prone to react with water and CO2 in the air to form Li2CO3, affecting its ionic conductivity and interface impedance, limiting its practical application.

Method used

Microwave heat treatment technology is used, bismuth oxide or molybdenum oxide is added as a modifier to repair the solid electrolyte in situ to form a Li-Bi/Mo-O structure coating with good ionic conductivity.

Benefits of technology

Effectively eliminate Li2CO3 on the solid electrolyte surface, improve its ionic conductivity and sintering density, reduce interface impedance, and improve the electrochemical performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005218475550000081
    Figure BDA0005218475550000081
  • Figure BDA0005218475550000091
    Figure BDA0005218475550000091
  • Figure HDA0005218475560000011
    Figure HDA0005218475560000011
Patent Text Reader

Abstract

The invention relates to a method for repairing a solid electrolyte, a solid electrolyte sheet and a battery. The method for repairing the solid electrolyte comprises the following steps: crushing the invalid solid electrolyte, adding a modifier, uniformly mixing, and carrying out microwave treatment to obtain the repaired solid electrolyte, the weight ratio of the failed solid electrolyte to the modifier is (98-99.75): (0.25-2.0); the modifier is bismuth oxide or molybdenum oxide; the solid electrolyte comprises Li5La3M2O12, and M is at least one of Zr, Nb, Ti, Ta, Sb, Mg, Sc, Zn, Ru, W or Te; and the failed solid electrolyte contains Li2CO3 (lithium carbonate). According to the invention, Li2CO3 on the surface of the solid electrolyte can be eliminated through a simple means, the compatibility with positive and negative electrode interfaces is obviously improved, and the interface impedance is reduced. The solid-state battery assembled by the electrolyte sheet after in-situ repair has excellent electrochemical performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of solid electrolyte repair, and relates to a method for repairing a solid electrolyte, a solid electrolyte sheet and a battery. Background Art

[0002] Solid electrolyte materials are the key to the development of solid-state lithium batteries. Garnet-type LLZO-based oxide solid electrolytes are considered to be the most promising lithium solid electrolytes due to their high ionic conductivity and relatively stable crystal structure. However, LLZO-based solid electrolytes are unstable in the air. During the synthesis and storage process, they easily react with water and CO2 in the air to generate Li2CO3 on their surface and grain boundaries, which will affect the sintering density of LLZO-based electrolyte ceramic sheets, thereby reducing the ionic conductivity of LLZO-based electrolytes. In addition, the low ionic conductivity of the Li2CO3 insulating layer will seriously affect the wettability between the LLZO-based electrolyte and the positive and negative electrode interfaces, resulting in high interfacial impedance. This limits the practical application of garnet-type solid electrolytes.

[0003] Prior art CN109728342A discloses a self-repairing composite solid electrolyte, a quasi-solid electrolyte and a lithium battery. The self-repairing composite solid electrolyte includes a self-repairing polymer and an inorganic solid electrolyte, and the self-repairing polymer includes a self-repairing group, and the self-repairing group is selected from a urea group. The self-repairing composite solid electrolyte of the invention is dry and bendable, flexible, and can inhibit the growth of lithium dendrites. The composite solid electrolyte has a self-repairing function that can increase the service life of the battery. A quasi-solid electrolyte prepared by adding a small amount of lithium salt-containing electrolyte to the self-repairing composite solid electrolyte can keep the electrolyte at a high conductivity, and at the same time reduce the content of the liquid electrolyte containing lithium salts, thereby improving the safety of the battery. However, it cannot handle solid electrolytes that have already generated Li2CO3.

[0004] Prior art CN113871675A discloses a method for repairing thin-film electrolytes of solid oxide batteries. A precursor salt solution doped with a ZrO2-based electrolyte is used to in-situ grow doped ZrO2-based nanoparticles on the sintered solid oxide battery thin-film electrolyte through a one-step hydrothermal reaction to make up for defects such as microcracks and pores, reduce cross-talk and leakage current, and achieve the repair of thin-film electrolytes. However, the reaction conditions of the hydrothermal reaction are very demanding, usually requiring very high pressure and temperature conditions. In addition, the hydrothermal reaction requires multiple subsequent purification steps, resulting in low yield and product quality, which is not conducive to industrial application. Summary of the invention

[0005] The purpose of the present invention is to provide a method for in-situ repairing a solid electrolyte, a solid electrolyte sheet and a battery, so as to solve the problems of poor air stability and large interface impedance of the solid electrolyte.

[0006] In order to achieve the above object, the present invention adopts the following technical solution:

[0007] A method for repairing a solid electrolyte comprises the following steps: crushing a failed solid electrolyte, adding a modifier, mixing evenly, and then subjecting the mixture to microwave treatment to obtain a repaired solid electrolyte; the weight ratio of the failed solid electrolyte to the modifier is 98-99.75:0.25-2.0; the modifier is bismuth oxide or molybdenum oxide; the solid electrolyte comprises Li5La3M2O 12 , M is at least one of Zr, Nb, Ti, Ta, Sb, Mg, Sc, Zn, Ru, W or Te; the failed solid electrolyte contains Li2CO3.

[0008] In one preferred embodiment, the solid electrolyte includes one or more of a LLZO-based composite material, a LLZTO-based composite material, a LLZNO-based composite material or a LLZGO-based composite material.

[0009] In one preferred embodiment, the solid electrolyte includes a composite material doped with Al, Fe, Ge or Ga at the Li position and a composite material doped with Sr, Y or Ce at the La position.

[0010] In a preferred embodiment, the mixing method is at least one of stirring, grinding, ball milling and shaking.

[0011] In one preferred embodiment, the microwave treatment includes a multi-mode resonant cavity and a 2000-3000 MHz microwave generator with an adjustable power of 0-2000W.

[0012] In a preferred embodiment, the microwave time is 3-10 min.

[0013] In one preferred embodiment, the microwave output power is 600W-950W.

[0014] Based on the same inventive concept, the present invention also claims protection for a solid electrolyte sheet obtained by sintering a repaired solid electrolyte, wherein the repaired solid electrolyte is obtained by a method for repairing a solid electrolyte.

[0015] In one preferred embodiment, the sintering temperature is 1200-1300° C., and the sintering time is 15-40 min.

[0016] In one preferred embodiment, the solid electrolyte sheet is obtained by pressing the repaired solid electrolyte into sheets to obtain an electrolyte green embryo; and then sintering the electrolyte green embryo.

[0017] In one preferred embodiment, the tabletting pressure is 250-350 MPa.

[0018] In one preferred embodiment, the diameter of the electrolyte embryo is 10-20 mm.

[0019] In one of the preferred embodiments, a small amount of mother powder is added during the sintering process, and the mother powder is an undeteriorated solid electrolyte.

[0020] Based on the same inventive concept, the present invention also claims protection for a symmetrical battery comprising the solid electrolyte sheet and a lithium sheet.

[0021] Based on the same inventive concept, the present invention also claims protection for an all-solid-state battery, comprising the solid electrolyte sheet, a positive electrode and a negative electrode.

[0022] In one preferred embodiment, the material of the positive electrode is any one of an oxide positive electrode material, a ternary positive electrode material, a sulfide positive electrode material or a spinel positive electrode material.

[0023] In one preferred embodiment, the oxide positive electrode material is any one of LiCoO2, LiFePO4 or LiMn2O4.

[0024] In one preferred embodiment, the ternary positive electrode material is any one of NCM or NCA.

[0025] In one preferred embodiment, the spinel positive electrode material is LiMn2O4 or LiNi 0.5 Mn 1.5 Any one of O4.

[0026] In a preferred embodiment, the material of the negative electrode is any one of metallic lithium, carbon material or silicon material.

[0027] The present invention will be further explained below:

[0028] Contains Li5La3M2O 12 When the solid electrolyte is placed in the air, a residual alkali passivation layer (Li2CO3) will be generated, which will affect the sintering density of the electrolyte ceramic sheet, thereby reducing the ionic conductivity of the electrolyte. The simple and efficient microwave heat treatment method and the introduction of in-situ modifiers (bismuth oxide or molybdenum oxide) can effectively repair the Li5La3M2O 12 Electrochemical properties of solid electrolytes. During microwave heat treatment, the in-situ modifier (bismuth oxide or molybdenum oxide) absorbs electromagnetic radiation to obtain energy and reacts with Li5La3M2O 12The residual alkali on the surface undergoes a conversion reaction to form a coating layer (lithium bismuthate or lithium molybdate) containing a Li-Bi / Mo-O structure with good ionic conductivity. The Lewis acidic Li-Bi / Mo-O structure layer promotes lithium ion transmission. Compared with the unrepaired solid electrolyte and the sintered repaired solid electrolyte, the ceramic sheet sintered by the repaired solid electrolyte powder has a stronger grain boundary bond and less porosity between grain boundaries, which is specifically reflected in the improved density of the ceramic block, higher ionic conductivity and lower activation energy.

[0029] Compared with the prior art, the present invention has the following beneficial effects:

[0030] 1. The present invention uses a small amount of modifier, which can eliminate Li2CO3 on the surface of the solid electrolyte by simple means and construct a fast ion conductor coating in situ. The solid electrolyte exhibits higher ionic conductivity and lower activation energy, and can improve the compatibility with the positive and negative electrode interfaces and reduce the interface impedance.

[0031] 2. The in-situ generated reaction of the present invention can be achieved in real time in the reaction system, without separation, and can act on the substrate in real time, thereby ensuring the sufficiency and completeness of the reaction; and the operation method is simple, with significant energy-saving advantages, and is a highly efficient and low-consumption heat treatment method.

[0032] 3. The solid-state battery assembled with the electrolyte sheet after in-situ repair has excellent electrochemical performance. The symmetrical battery cycle exceeds 500 hours, and the all-solid-state battery can stably cycle 200 times at a rate of 0.2C at room temperature, which is a significant improvement compared to before repair. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 1 is a SEM image and an EDS elemental analysis image of the repaired LLTZO solid electrolyte powder in Example 1 of the present invention; in the figure, a is a SEM image of the repaired LLTZO solid electrolyte powder, b is an EDS elemental analysis overall image, c is an O elemental analysis image, d is a La elemental analysis image, e is a Ta elemental analysis image, f is a Zr elemental analysis image, and g is a Bi elemental analysis image;

[0034] Figure 2 FTIR images of the repaired LLTZO solid electrolyte powder in Example 1 of the present invention and Comparative Example 1;

[0035] Figure 3 is a SEM image of the repaired LLTZO solid electrolyte ceramic sheet in Example 1, Comparative Example 1 and Comparative Example 2 of the present invention;

[0036] Figure 4Graphs of ionic conductivity and activation energy of the LLTZO solid electrolyte ceramic sheets repaired in Example 1 of the present invention and Comparative Example 1;

[0037] Figure 5 The performance of the symmetrical battery assembled with the repaired LLTZO solid electrolyte ceramic sheets in Example 1 of the present invention and Comparative Example 1;

[0038] Figure 6 The performance of the all-solid-state battery assembled with the repaired LLTZO solid electrolyte ceramic sheets according to Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0039] The present invention is not limited to the following specific embodiments. A person skilled in the art can implement the present invention in various other specific embodiments according to the contents disclosed in the present invention, or any simple changes or modifications made to the design structure and ideas of the present invention fall within the protection scope of the present invention. It should be noted that the embodiments and features in the embodiments of the present invention can be combined with each other without conflict.

[0040] Example 1

[0041] (1) The LLZTO electrolyte powder was placed in air for 50 days to generate Li2CO3 on its surface, which was named LLZTO@Li2CO3-50d.

[0042] (2) Weigh 2 g of LLZTO@Li2CO3-50d obtained in step (1), add 0.01 g of Bi2O3, and grind the mixture thoroughly in a mortar.

[0043] (3) The powder obtained in step (2) is placed in a crucible and heat treated by a microwave treatment device. The microwave output power is stabilized at 800 W and the microwave time is 6 min. The treated powder is ground evenly to obtain a repaired LLZTO@Li2BiO3 electrolyte powder. The SEM image and elemental analysis of the repaired LLZTO@Li2BiO3 electrolyte powder are shown in FIG. Figure 1 As shown in the figure, a is the SEM image of the repaired LLTZO solid electrolyte powder, b is the EDS element analysis diagram, c is the O element analysis diagram, d is the La element analysis diagram, e is the Ta element analysis diagram, f is the Zr element analysis diagram, and g is the Bi element analysis diagram. It shows that Li2BiO3 exists on the surface, the conversion is successful, and the distribution is uniform.

[0044] (4) The powder obtained in step (3) was placed in a mold with a diameter of 18 mm, and was pressed into a tablet under a pressure of 300 MPa to obtain an electrolyte embryo. 1 g of mother powder (undeteriorated LLZTO electrolyte powder) was placed in a platinum crucible, and the pressed green embryo was placed on the mother powder. The crucible was sealed with a platinum cover and heated to 1250° C. at a heating rate of 5° C. / min for 30 min to obtain an LLZTO electrolyte ceramic sheet. The SEM image of the LLZTO electrolyte ceramic sheet is as follows: Figure 3 It can be seen that the surface coating of the grains inside the repaired ceramic sheet is dense and uniform, the grain boundary bonding is relatively firm, and the porosity between the grain boundaries is small, indicating that the density of the ceramic block has been improved. This result proves that Bi2O3 repair of LLZTO@Li2BiO3 can effectively improve the sintering density of LLZTO electrolyte and promote the sintering of LLZTO.

[0045] (5) The ceramic sheet obtained in step (4) was polished with 1200 mesh and 2000 mesh sandpaper, and then coated with conductive silver paste on both sides. AC impedance test was performed, and the ionic conductivity and activation energy of the corresponding ceramic sheet were obtained by impedance calculation, such as Figure 4 As shown in the figure, the ionic conductivity is Figure 4 a, activation energy diagram Figure 4 b.

[0046] (6) The electrolyte sheet obtained in step (4) and a lithium metal sheet with a thickness of 450 μm were assembled into a symmetrical battery, and the electrochemical performance of the battery was tested. The results were as follows: Figure 5 shown.

[0047] (7) A lithium metal button-type all-solid-state battery with a high-nickel ternary positive electrode (NCM811) was assembled in the stacking order of the positive electrode sheet, the solid electrolyte sheet, and the negative electrode, and the electrochemical performance of the battery was tested. The results are as follows: Figure 6 shown.

[0048] Example 2

[0049] Compared with Example 1, the difference is that the amount of Bi2O3 added in step (2) is changed to 0.005g.

[0050] The ionic conductivity and activation energy of the LLZTO electrolyte ceramic sheet of this embodiment were tested, and the test results are shown in Table 1.

[0051] Example 3

[0052] Compared with Example 1, the difference is that the amount of Bi2O3 added in step (2) is changed to 0.02g.

[0053] The ionic conductivity and activation energy of the LLZTO electrolyte ceramic sheet of this embodiment were tested, and the test results are shown in Table 1.

[0054] Example 4

[0055] Compared with Example 1, the difference is that the amount of Bi2O3 added in step (2) is changed to 0.04g.

[0056] The ionic conductivity and activation energy of the LLZTO electrolyte ceramic sheet of this embodiment were tested, and the test results are shown in Table 1.

[0057] Example 5

[0058] Compared with Example 1, the difference is that the microwave output power of step (3) is changed to 600W.

[0059] The ionic conductivity and activation energy of the LLZTO electrolyte ceramic sheet of this embodiment were tested, and the test results are shown in Table 1.

[0060] Example 6

[0061] Compared with Example 1, the difference is that the microwave output power of step (3) is changed to 950W.

[0062] The ionic conductivity and activation energy of the LLZTO electrolyte ceramic sheet of this embodiment were tested, and the test results are shown in Table 1.

[0063] Example 7

[0064] Compared with Example 1, the difference is that the microwave time in step (3) is changed to 3 minutes.

[0065] The ionic conductivity and activation energy of the LLZTO electrolyte ceramic sheet of this embodiment were tested, and the test results are shown in Table 1.

[0066] Example 8

[0067] Compared with Example 1, the difference is that the microwave time in step (3) is changed to 10 min.

[0068] The ionic conductivity and activation energy of the LLZTO electrolyte ceramic sheet of this embodiment were tested, and the test results are shown in Table 1.

[0069] Example 9

[0070] Compared with Example 1, the difference is that Bi2O3 in step (2) is replaced by MoO3.

[0071] The ionic conductivity and activation energy of the LLZTO electrolyte ceramic sheet of this embodiment were tested, and the test results are shown in Table 1.

[0072] Comparative Example 1

[0073] (1) The LLZTO electrolyte powder was placed in air for 50 days to generate Li2CO3 on its surface, which was named LLZTO@Li2CO3-50d.

[0074] (2) Weigh 2 g of LLZTO@Li2CO3-50d obtained in step (1) and grind it thoroughly in a mortar. The FTIR image of LLZTO@Li2CO3-50d is shown in Figure 2 shown.

[0075] (3) The powder obtained in step (2) was placed in a mold with a diameter of 18 mm, and was pressed into a tablet under a pressure of 300 MPa to obtain an electrolyte embryo. 2 g of the mother powder was placed in a platinum crucible, and the pressed embryo was placed on the mother powder. The crucible was sealed with a platinum cover and heated to 1250°C at a heating rate of 5°C / min and kept warm for 30 min to obtain an LLZTO electrolyte ceramic sheet. The SEM image of the LLZTO electrolyte ceramic sheet is as follows: Figure 3 As shown in b, it can be seen that the internal grains of the LLZTO electrolyte ceramic sheet of comparative example 1 are polyhedral, and there are large pores between the grain boundaries, indicating that its density is low.

[0076] (4) The ceramic sheet obtained in step (3) was polished with 1200 mesh and 2000 mesh sandpaper, and then coated with conductive silver paste on both sides. AC impedance test was performed, and the ionic conductivity and activation energy of the corresponding ceramic sheet were obtained by impedance calculation, as shown in Table 1 and Figure 4 As shown in the figure, the ionic conductivity is Figure 4 a, activation energy diagram Figure 4 b.

[0077] (5) Assembling a symmetrical battery with the electrolyte sheet obtained in step (3) and a lithium metal sheet with a thickness of 450 μm, and testing the electrochemical performance of the battery, such as Figure 5 As shown, the symmetrical battery of Comparative Example 1 can be seen.

[0078] Comparative Example 2

[0079] (1) The LLZTO electrolyte powder was placed in air for 50 days to generate Li2CO3 on its surface, which was named LLZTO@Li2CO3-50d.

[0080] (2) Weigh 2 g of LLZTO@Li2CO3-50d obtained in step (1), add 0.01 g of B2O3, and grind the mixture thoroughly in a mortar.

[0081] (3) The powder obtained in step (2) is placed in a crucible, the sintering temperature is 600° C., the sintering time is 5 h, the heating rate is 5° C. / min, and the sintered powder is ground evenly to obtain the repaired LLZTO@Li2BO3 electrolyte powder.

[0082] (4) The powder obtained in step (3) was placed in a mold with a diameter of 18 mm, and was pressed into a tablet under a pressure of 300 MPa to obtain an electrolyte embryo. 1 g of mother powder (undeteriorated LLZTO electrolyte powder) was placed in a platinum crucible, and the pressed green embryo was placed on the mother powder. The crucible was sealed with a platinum cover and heated to 1250°C at a heating rate of 5°C / min and kept warm for 30 min to obtain an LLZTO electrolyte ceramic sheet. The SEM image of the LLZTO electrolyte ceramic sheet is as follows: Figure 3 As shown in c. It can be seen that the coating layer attached to the surface of the grains inside the LLZTO electrolyte ceramic sheet of comparative example 2 is sparse and uneven, and although the density is improved to a certain extent, there are still holes caused by grain fusion due to long-term sintering.

[0083] (5) The ceramic sheet obtained in step (4) was polished with 1200 mesh and 2000 mesh sandpaper, and then coated with conductive silver paste on both sides. AC impedance test was performed, and the ionic conductivity and activation energy of the corresponding ceramic sheet were obtained by impedance calculation (as shown in Table 1).

[0084] Comparative Example 3

[0085] Compared with Example 1, the difference is that the amount of Bi2O3 added in step (2) is changed to 0.06g.

[0086] The ionic conductivity and activation energy of the LLZTO electrolyte ceramic sheet of this embodiment were tested, and the test results are shown in Table 1.

[0087] Comparative Example 4

[0088] Compared with Example 1, the difference is that the microwave time in step (3) is changed to 15 min.

[0089] The ionic conductivity and activation energy of the LLZTO electrolyte ceramic sheet of this embodiment were tested, and the test results are shown in Table 1.

[0090] The FTIR image of the repaired LLZTO@Li2BO3 electrolyte powder in Comparative Example 4 is as follows Figure 3 shown.

[0091] Comparative Example 5

[0092] Compared with Example 1, the difference is that the microwave output power of step (3) is changed to 1200W.

[0093] The ionic conductivity and activation energy of the LLZTO electrolyte ceramic sheet of this embodiment were tested, and the test results are shown in Table 1.

[0094] Comparative Example 6

[0095] Compared with Comparative Example 2, the difference is that B2O3 in step (2) is replaced by Bi2O3.

[0096] The ionic conductivity and activation energy of the LLZTO electrolyte ceramic sheet of this embodiment were tested, and the test results are shown in Table 1.

[0097] Comparative Example 7

[0098] Compared with Example 1, the difference is that Bi2O3 in step (2) is replaced by B2O3.

[0099] The ionic conductivity and activation energy of the LLZTO electrolyte ceramic sheet of this embodiment were tested, and the test results are shown in Table 1.

[0100] The ionic conductivity and activation energy of the electrolyte ceramic sheets of the embodiments and comparative examples are summarized as follows:

[0101] Table 1 Performance test results of Examples 1-9 and Comparative Examples 1-5

[0102]

[0103]

[0104] From the test results of Comparative Example 1 and Example 1 in Table 1, the ionic conductivity of the repaired LLZTO electrolyte is significantly improved and the activation energy is reduced compared with the LLZTO@Li2CO3-50d ceramic sheet. Figure 5 The data of symmetrical cells assembled with lithium metal show that the repaired LLZTO electrolyte sheet has a better negative electrode interface. Compared with the repaired LLZTO ceramic sheet, the activation energy of the LLZTO@Li2CO3-50d ceramic sheet is higher, indicating that the Li + The energy barrier of migration is higher, which proves that Li2CO3 will limit the Li + migration. Figure 2 It can be seen that compared with LLZTO@Li2CO3-50d, the absorption peak intensity of Li2CO3 in the repaired sample is significantly weakened, and the absorption peak of LiBiO3 appears, proving that Li2CO3 on the surface of LLZTO reacts with Bi2O3 to generate LiBiO3. However, if the microwave heat treatment time is too long and the microwave output power is too high during the repair process, the temperature during the heat treatment process will increase, which will aggravate the decomposition of LLZTO and lead to the generation of more impurities; in addition, the results of comparative example 3 show that when the addition amount of Bi2O3 is too large, it will also reduce the ionic conductivity of the electrolyte and increase the energy barrier that needs to be overcome during the ion migration process. This may be because adding too much Bi2O3 will aggravate the decomposition of LLZTO during the sintering process, leading to the occurrence of side reactions.

[0105] It should be noted that the above embodiments are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the embodiments here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.

Claims

1. A method for repairing a solid electrolyte, characterized in that: The following steps are involved: The failed solid electrolyte is crushed, a modifier is added, mixed evenly, and then microwaved to obtain a repaired solid electrolyte; The weight ratio of the failed solid electrolyte to the modifier is 98-99.75:0.25-2.0; the modifier is bismuth oxide or molybdenum oxide; the solid electrolyte includes Li5La3M2O 12 , M is at least one of Zr, Nb, Ti, Ta, Sb, Mg, Sc, Zn, Ru, W or Te; the failed solid electrolyte contains Li2CO3.

2. The method according to claim 1, characterized in that The solid electrolyte includes one or more of a LLZO-based composite material, a LLZTO-based composite material, a LLZNO-based composite material or a LLZGO-based composite material.

3. The method according to claim 1, characterized in that: The solid electrolyte comprises a composite material doped with Al, Fe, Ge or Ga at the Li position and a composite material doped with Sr, Y or Ce at the La position.

4. The method according to any one of claims 1 to 3, characterized in that: The microwave time is 3-10min; the microwave output power is 600W-950W.

5. A solid electrolyte sheet, characterized in that: The repaired solid electrolyte is obtained by sintering, and the repaired solid electrolyte is obtained by the method for repairing a solid electrolyte according to any one of claims 1 to 4.

6. The solid electrolyte sheet according to claim 5, characterized in that: The sintering temperature is 1200-1300°C, and the sintering time is 15-40 minutes.

7. The solid electrolyte sheet according to claim 5, characterized in that: The solid electrolyte sheet is obtained by pressing the repaired solid electrolyte into sheets to obtain an electrolyte green embryo; and then sintering the electrolyte green embryo.

8. The solid electrolyte sheet according to claim 7, characterized in that: The tableting pressure is 250-350 MPa.

9. A symmetrical battery, characterized in that: It comprises the solid electrolyte sheet and lithium sheet as described in any one of claims 5 to 8.

10. An all-solid-state battery, characterized in that: The invention comprises the solid electrolyte sheet, a positive electrode and a negative electrode as described in any one of claims 5 to 8.

Citation Information

Patent Citations

  • Self-repairing composite solid electrolyte, quasi-solid electrolyte and lithium battery

    CN109728342A

  • Method for repairing thin film electrolyte of solid oxide battery

    CN113871675A